Massive hemoptysis. Selective embolization of bronchial artery-left pulmonary artery fistula - Federico Liberman; Nicolás Zaderenko; Guillermo Pacheco; Juan Pablo Casas; José Lugones (REC: Interventional Cardiology (English Ed.), 2023)
CASE PRESENTATION Hemoptysis is the subglottal expectoration of blood from the tracheobronchial tree. Most cases of massive hemoptysis originate at the bronchial arteries (90%) and often become complicated due to systemic arterial blood pressure. The mechanism of action is the rupture of hypervascularized reticulum and vascular dilatation as a response to the substances released in the inflammatory process. This clinical entity has elevated morbidity and mortality rates. Early diagnosis and the timely administration of therapy are of paramount importance. This is the case of a 73-year-old woman with a past medical history of breast cancer with ED presentation of early onset massive hemoptysis. She was admitted to the intensive care unit with a heart rate of 122 bpm, arterial blood pressure of 78/45 mmHg, and oxygen saturation of 82% with high-flow oxygen mask. Emergency orotracheal intubation and mechanical ventilation were decided. Given the patient’s hemodynamic instability, vasopressor drug infusion was started at increasing doses until a mean arterial blood pressure of 60 mmHg was reached with noradrenalin at 0.3 µg/kg/min. Lab test results showed hemoglobin levels of 7.5 g/dL, hematocrit of 21%, PaO2 of 62%, and hyperlactacidemia. A total of 2 bags of packed red blood cells were transfused, and the patient...